Audience memory as evidence in the trial on the Crown - Westwood, G (De Gruyter, 2022)
This chapter takes its cue from the curious near-absence of formal witness testimony in the extant speeches from the trial on the Crown in 330 BC (Aeschines, Against Ctesiphon; Demosthenes, On the Crown). It argues that both orators base their cases on the understanding that the trial audience – above all, the judges – could act as proxy witnesses because many of them had experienced events central to Aeschines’ prosecution, namely Demosthenes’ policy of resistance to Macedon and his public activities before, during, and after the war of 340–338 BC. But whereas Aeschines largely just assumes that the judges will accept his negative versions of these events and activities, Demosthenes overtly mobilises the judges’ personal memories, and in a positive direction. The judges’ status as “witnesses” therefore becomes a powerful way for him to assert both the appropriateness of the honours proposed for him by Ctesiphon and, consequently, Ctesiphon’s innocence on Aeschines’ main charge.